(untitled) (Architecture Image Studies, 2025)
This article explores an operational management model for desilting the Poechos Dam in Chira-Piura, considering the sedimentation rate, which is decreasing by 1% annually, significantly impacting water availability for irrigation, drinking, and hydroelectric power generation in northern Peru. The research was basic, descriptive, cross-sectional, and non-experimental. Two questionnaires, validated by five experts, were used as instruments, each with 23 items for the two variables and a Likert scale. The main findings include frequency tables that reveal a lack of information and uncertainty regarding desilting procedures. This is corroborated in the results discussion by studies conducted in the Moquegua region, such as Romero’s 2022 work, and at the Gallito Ciego Dam, by Matute-Velásquez, also in 2022. The discussion incorporates ideas from the Integrated Water Resources Management Model Theory and the adoption of Lean practices, suggesting an organized approach to achieving transparency and sustainability. The proposed model aligns with SDGs 6 and 9, contributing to the 2030 Agenda through reservoir restoration and climate resilience. The conclusions highlight perception neutrality as an opportunity for training, positioning the work as a benchmark for water management in Latin America.